Risk assessment of mercury and methyl mercury intake via sardine and swordfish consumption in Algeria - MEHOUEL, F.; BOUAYAD, L.; BERBER, A.; VAN HAUTEGHEM, I.; VAN DE WIELE, M. (Journal of the Hellenic Veterinary Medical Society, 2019)
Total mercury (Hg) and methylmercury (MeHg) concentrations in the flesh of sardine (Sardina pilchardus) and swordfish (Xiphias gladius) fished in three Algerian coasts were determined by a direct mercury analyzer (DMA). We also assessed the risk to which the consumer was exposed to by calculating the estimated daily intakes (EDIs), target hazard quotient (THQ) and hazard index (HI). The average concentrations of Hg and MeHg in the flesh of sardine were similar (0.04 mg/kg wet weight) and in swordfish were 0.61 mg/kg wet weight; 0.57 mg/kg wet weight, respectively. These concentrations have not surpassed the thresholds set by the Algerian and European regulations. The estimated daily intakes for Hg and MeHg were similar in sardine (0.0064 μg/kg/day) and were 0.098 μg/kg/day and 0.092 μg/kg/day for Hg and MeHg, respectively, in swordfish. These values did not exceed the provisional tolerable weekly intake (PTWI) established by the European Food Safety Authority (EFSA) and by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). The target hazard quotient (THQ) and the hazard index (HI) calculated were < 1. Consequently, consumption of these fishes does not pose any risk for the adult groups of the Algerian population regarding mercury, and methylmercury studied.